ANALISIS GANGGUAN PENDENGARAN PADA PEKERJA PEMOTONG RUMPUT AKIBAT KEBISINGAN DARI MESIN PEMOTONG RUMPUT TAHUN 2014 - Defri Erman; Sukendi ' Sukendi; Suyanto ' Suyanto (Program Pascasarjana Universitas Riau, 2014)
This study aims to analyze and examine the effect of job tenure, length of employment,and the age of workers mower against hearing loss due to noise generated by the lawnmower. This study used a cross-sectional approach, with a total sampling usingsampling as many as 30 workers cutting the grass in the town of Thorns. Theindependent variable of this study is the intensity noise (dB), tenure (years), duration ofwork (hours), and the age of workers mower. The analysis was performed usingunivariate and bivariate.The results showed there is 1 variable that affects the functionof the auditory capacities of workers mower, lawn mower that worker's age (p value:0.002,  2 : 9600, CL: 0.005-0.464). From the bivariate analysis showed that age ofmower workers is the most dominant disorder that affects hearing loss on mowerworkers.